Problematika Pembelajaran Bahasa Arab di Madrasah Aliyah Islamiyah Attanwir - Na'im, Tsalisa Miftah Nur (Maliki Interdisciplinary Journal, 2024)
Arabic language learning at Madrasah Aliyah Islamiyah Attanwir faces various issues that hinder its effectiveness. The main challenges include a lack of student motivation, limited teacher competence, irrelevant teaching materials, and inadequate facilities. This article discusses these challenges and offers strategic efforts to address them, including enhancing teaching methods, training for teachers, adjusting materials, and optimizing educational facilities. Through these measures, it is expected that Arabic language learning can be more effective and provide maximum benefits for students.